Comparative study of urban and rural operation and maintenance practices of water distribution systems at Kai !Garib Municipality - Muinamia, Eva Wanjiru (Department of Civil Engineering, 2016)
The South African Government has invested heavily in the provision of water to its citizens. These efforts are however futile if appropriate operation and maintenance (O&M) plans are not put in place to ensure sustainability of the infrastructure. The operation and maintenance requirements of rural areas differ from those of urban areas due to differences in demand patterns, lengths of mains and consumer densities. This study investigated O&M practices in both rural and urban areas in the Kai !Garib local municipality. The study applied selected performance indicators from the International Water Association and the Regulatory Performance Measurement System (Department of Water Affairs) to evaluate and compare the performances of the selected rural and urban systems. The study also used questionnaires administered to the technical personnel in the municipality to attain more detailed information on the O&M practices. It was found that the urban areas had more varied O&M practices. The urban systems were also found to have more resources and personnel dedicated to O&M than the rural systems.